Factors That Affected Labor Productivity on Production Department at PR Gagak Hitam Pakuniran Bondowoso Regency - Laylia, Siti Jamilatul; Dhamayanthi, Wenny; Puspitorini, Ratih (Politeknik Negeri Jember, 2023)
The company should always strive to maintain and improve the labor productivity to maintain and achieve the goal that has been achieved so that the company can continue to operate effectively and efficiently with existing resources and produce products as expected. Increasing productivity is necessary because without a high labor productivity it is difficult for companies to achieve the set target. The aim of this study was to (1) Determine and analyze the influence of work environment, job stress, skills, motivation to work productivity of employees Cigarette Production section simultaneously at PR Gagak Black Pakuniran Maesan . (2) To know and analyze the influence of work environment, job stress, skills, motivation to employees productivity partially Cigarette Production section at PR Gagak Black Pakuniran Maesan. (3) To determine and analyze the variables which had dominant influence to the employees productivity on cigarette production section at PR Gagak Black Pakuniran Maesan. The research took 3 (three) months, which was located at PR Gagak Black Pakuniran Maesan . The method that used in the final assignment was survey research by using questionnaires (questionnaire) as a tool for collecting data. The results of this study showed that Work Environment (X1) Work Stress (X2) Skills (X3) Motivation (X4) simultaneously had a significant effect on labor productivity, and Work Stress (X2) Skills (X3) does not have a significant effect on labor productivity. Work Environment (X1) Motivation (X4) partially has a significant effect on labor productivity.